PENINGKATAN HASIL BELAJAR BANGUN DATAR DENGAN MODEL DISCOVERY LEARNING BERBANTUAN PAWTOON PADA SISWA KELAS V SD NEGERI 05 TAROK DIPO KOTA BUKITTINGGI - Hamda Yani Putri; Salmaini, Salmaini; Ahmad, Syafri; Ulya Akmal, Atika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low mathematics learning outcomes of fifth-grade students at sdn 05 tarok dipo, bukittinggi, on the topic of plane figures, which resulted from teacher-centered learning and the suboptimal use of instructional media. This study aimed to improve students' mathematics learning outcomes through the implementation of the discovery learning model assisted by powtoon media. This research employed a classroom action research (car) design using qualitative and quantitative approaches. The study was conducted in two cycles, with cycle i consisting of two meetings and cycle ii consisting of one meeting, involving 21 fifth-grade students. Each cycle included the stages of planning, implementation, observation, and reflection. Data were collected through observation, tests, and non-test techniques. The findings revealed that the implementation of the discovery learning model assisted by powtoon media improved both the learning process and students' learning outcomes. The average lesson plan score increased from 95 to 98, teacher activity improved from 83 to 97, and student activity increased from 78 to 96. Meanwhile, the average student learning outcomes improved from 76 and 82 in cycle i to 91 in cycle ii, with classical learning mastery reaching 100%. Therefore, the discovery learning model assisted by powtoon media was proven to be effective in improving the mathematics learning outcomes of fifth-grade students at sdn 05 tarok dipo, bukittinggi.